Comparative study of trabeculectomy using single sutures versus releasable sutures - Matlach, Juliane (Dove Medical Press, 2012)
BACKGROUND: The purpose of this study was to compare the outcomes of trabeculectomy using single sutures or releasable sutures. METHODS: This retrospective study analyzed the medical records of 61 patients who had undergone trabeculectomy using single sutures (n = 33, 54.1%) or releasable sutures (n = 28, 45.9%). The scleral flap was secured with a mean 3.9 (range 3–5) single sutures in 33 patients and with three releasable sutures in 28 patients. Primary outcomes were the success rate, based on intraocular pressure and medication usage, and the frequency of complications and post-surgical interventions. The criteria used to determine complete success were, first, intraocular pressure < 18 mmHg and, second, ≤21 mmHg and ≥20% intraocular pressure reduction without glaucoma medication. RESULTS: All patients had an intraocular pressure ≤ 21 mmHg; 87.5% in the single suture group and 92.6% in the releasable suture group had an intraocular pressure < 18 mmHg at 24 months. There was a highly significant reduction in intraocular pressure to baseline values in both groups at the last visit. Applying the first criterion, complete success was achieved in 57.6% of patients with single sutures and 71.4% with releasable sutures, and based on the second criterion, 66.7% and 71.4%, respectively. No significant difference was found between the groups with regard to intraocular pressure, or success or complication rates. CONCLUSION: The results of trabeculectomy using single sutures or releasable sutures are equivalent. Therefore, the choice of suture technique should be based on individual patient requirements and surgeon experience.